Influence of Bond Pattern on the in-plane Behavior of URM Piers. Issue 10 (3rd October 2021) - Malomo, D.; DeJong, M.J.; Penna, A.
ABSTRACT: The overall seismic resistance of unreinforced masonry (URM) systems that exhibit box-behavior mainly relies on the lateral force capacity of structural components. Despite the fact that it is widely accepted that masonry bond pattern might considerably affect the in-plane performance of URM members, this aspect has not fully addressed experimentally or numerically. In this paper, calibrated numerical models, developed within the framework of the Distinct Element Method, are used to simulate the quasi-static lateral response of URM piers under several combinations of boundary conditions, vertical pressures and aspect ratios, as well as a large number of typically-employed periodic and quasi-periodic bond patterns. The employment of time, size and mass scaling, and dynamic relaxation procedures, combined with the introduction of equivalent interface properties to represent the effect of cyclic damage through monotonic loading schemes, provided a significant reduction of computational cost, thus enabling a comprehensive parametric study to be carried out within an acceptable timeframe. The results show that the bond pattern has an appreciable influence on the response of laterally-loaded URM panels, motivating the possibility of including this aspect in the assessment of existing URM structures. Analytical formulations were also inferred by fitting numerical data, thus enabling the findings of this work to be readily implemented in assessment using simplified models.